2018
DOI: 10.1002/imhj.21742
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and Their Infants Co‐admitted to a Newly Developed Mother–baby Unit: Characteristics and Outcomes

Abstract: Research on Mother-Baby Units (MBUs) has mainly focused on maternal psychiatric outcomes, not the well-being of infants. This study investigated infant development and mental health along with maternal characteristics and the mother-infant relationship in 45 dyads (60% New Zealand European, 20% Māori, 11% Pacific) admitted to a new MBU. Maternal psychopathology was measured with the Health of the Nations Outcome Scale (HoNOS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
15
1
1
Order By: Relevance
“…All women were referred by community-based, maternal mental health (MMH) teams and had infants under 1 year of age. Comprehensive description of the service and therapeutic interventions has been previously reported (Wright et al, 2018). Consent to participate in this study was sought by research assistants when the clinical team had determined that the maternal mental state was sufficient to enable competent informed consent.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…All women were referred by community-based, maternal mental health (MMH) teams and had infants under 1 year of age. Comprehensive description of the service and therapeutic interventions has been previously reported (Wright et al, 2018). Consent to participate in this study was sought by research assistants when the clinical team had determined that the maternal mental state was sufficient to enable competent informed consent.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The GAF was determined by the treating psychiatrist at admission, discharge, and follow-up. We have previously reported the positive correlation between GAF and routine outcome collection using the Health of the Nation Outcome scale (Wright et al, 2018) and our preference to employ GAF because it allows greater recognition of the relationship with the infant and maternal caregiving within functioning.…”
Section: Maternal Psychopathology and Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising given that electronic screening facilitates disclosure in perinatal settings and in one study, 69% reported they were glad to be asked and 87% took it as evidence their provider cared about them. 16 Other perinatal studies in New Zealand with participants with higher burdens of psychopathology have had considerably higher participation, 17 suggesting that MatCHAT may not have been a sufficiently relational approach to facilitate participation. Alternatively, the timing (over the holiday period, which is renowned for lower staffing) and short duration of this study likely contributed to poor uptake by both midwife and perinatal participants.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders may also be associated with deficits in caring for the newborn baby and disruptions in the mother–baby relationship 1–3. Over the longer term, the children of mothers admitted to inpatient psychiatric services may develop a range of health, developmental and mental health concerns 4. A recent examination of the costs of perinatal mental health problems indicates that the greatest costs relate to adverse child outcomes 5…”
Section: Introductionmentioning
confidence: 99%